Development and integration of creative drama-based activities to enhance the oral communication skills in English of intermediate pupils - Maglaya, Rommel (The Scholastican Journal, 2012)
The study aimed to develop and integrate creative drama-based activities in English language lessons as a tool to enhance the oral communication skills of intermediate pupils. It was found out that creative drama-based activities could enhance the oral communication skills of intermediate pupils. It was found out that creative drama-based activities could enhance the oral communication skills since pupils became more comfortable in speaking in front of the class and in expressing themselves using English as medium for oral communication. Hence, the activities helped promote the building of self-confidence. Creative drama-based activities also provided an ideal opportunity for timid children to overcome their inhibitions; it guided insensitive children to some awareness of the feelings of others and broadened the horizon of all participants.